2017
DOI: 10.1016/j.colsurfa.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Permeation of pharmaceutical compounds through silicone membrane in the presence of surfactants

Abstract: This study reports the effect of surfactant charge and concentration on the permeation of four model compounds (benzocaine, benzotriazole, ibuprofen and lidocaine). Surfactant charge was systematically varied using a range of surfactants that are known to possess specific head group charges, namely an anionic, a cationic, a zwitterionic and a neutral form over a series of surfactant concentrations, i.e. where possible, both above, and below, the critical micellar concentration for each surfactant. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…At the higher oil concentration, again flux improves with initial increase in surfactant concentration and then reduces with further increase in surfactant concentration. These results further prove that the increase of surfactant concentration over a specific limit retards the permeation of lidocaine as presented in literature [ 52 , 60 ]. These observations confirmed the benefit of PDMS membrane in screening the formulation variables before testing on the skin.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…At the higher oil concentration, again flux improves with initial increase in surfactant concentration and then reduces with further increase in surfactant concentration. These results further prove that the increase of surfactant concentration over a specific limit retards the permeation of lidocaine as presented in literature [ 52 , 60 ]. These observations confirmed the benefit of PDMS membrane in screening the formulation variables before testing on the skin.…”
Section: Resultssupporting
confidence: 89%
“…At higher surfactant concentration, however, flux became higher which will be discussed later. On another note, the maximum amount that was able to permeate through the membrane after 6 h was found to be 394.04 µg/cm 2 , whereas in this study reached higher than 1000 µg/cm 2 [ 52 ]. Waters et al also showed similar results in which the highest flux value obtained was 118.4 µg/h/cm 2 which is similar to those obtained in this study.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Examples include mathematical models (Mitragotri et al, 2011), human skin equivalents (Schmook et al, 2001) and chromatographic based methods (Waters et al, 2013b), a summary of the main proposed methods can be found in (L Waters, 2015). A reliable membrane to employ as a skin mimic is poly(dimethylsiloxane), also known as PDMS, which has been the focus of several research groups in recent years (Bhuiyan and Waters, 2017;Luo et al, 2016;Rodríguez-López et al, 2019;Shahzad et al, 2014;Waters and Bhuiyan, 2016;Waters et al, 2013a;Watkinson et al, 2009). PDMS has a silicon-oxygen backbone with a very high bond energy providing high thermal stability, i.e.…”
Section: Introductionmentioning
confidence: 99%